Kisah Musa dan Firaun dalam Tafsir Al-Manār: Paradigma Qur’ani Melawan Otoritarianisme dan Tirani Kekuasaan - Muhammad Rafsanjani; Ulfatul Halimah (Indo Publishing, 2025)
This article aims to examine the Prophet Moses and Pharaoh as interpreted in Tafsir al-Manār by Muhammad Rashid Rida, with the intent to uncover the Qur'anic paradigm in addressing the phenomenon of authoritarianism and tyranny. Employing a qualitative approach with thematic exegesis as the primary analytical instrument, this study explores how Rida not only presents the historical dimensions of the narrative but also articulates it as a socio-political critique of despotic regimes that undermine human dignity and justice. Tafsir al-Manār positions the story of Moses and Pharaoh not merely as a spiritual-religious narrative, but as a reflection of the dynamics of power that deviate from ethical principles and divine norms. Moses’ rejection of Pharaoh’s domination is interpreted as a symbol of resistance against all forms of absolute power that violate human rights and dignity. Accordingly, this tafsir presents a normative Qur'anic framework relevant to the formulation of a political system that is just, transparent, and rooted in humanitarian values. Through this analysis, the article seeks to contribute to the development of thematic exegesis discourse that promotes social transformation and encourages a contextual, critical, and responsive reading of the Qur'an in light of contemporary political challenges. This study concludes that Tafsir al-Manār offers a Qur’anic critique of tyrannical authority and proposes an Islamic political paradigm that is just, humanistic, and transformative...